Ciągłość i zmiana w polityce zagranicznej Francji w okresie prezydentury François Hollande’a — wybrane aspekty - Lakomy, Miron (Studia Politicae Universitatis Silesiensis, 2017)
Abstract: Continuation and change in the French foreign policy during the presidency of François Hollande — selected aspects François Hollande became a president of the 5th French Republic in a difficult moment for its international interests. In Europie, Africa and the Middle East, France had to face multiple unfavorable events and processes. Instability in the Arab states, civil war in Syria and Mali or eurozone crisis had major importance for the French international status and security. In this context, it is important to consider, what kind of approach to these challenges was adopted by the new president? Furthermore, did he remain faithful to the traditional fundaments of the French foreign policy? Therefore, this article is an analysis of the elements of continuity and change in the diplomacy of the 5th Republic between May 2012 and October 2013, basing on its European, American, African and Arab policy. Key words: French foreign policy, continuation, change